Investigation Of Metal Organic Deposition Derived Cerium Oxide Thin Films On Silicon Wafer - Jasni, Farah Anis (2009)

(untitled)
Cerium oxide (CeO2) thin films have been formed on silicon (Si) substrates via metal organic decomposition route in order to resolve the usefulness of this oxide as an alternative gate dielectric for Si-based metal-oxide-semiconductor (MOS) applications. Salts of cerium(III) nitrate and cerium(III) acetylacetonate were independently used as the starting material with the addition of methanol and acetic acid to form a constant concentration of 0.25 M. Solution was spin coated on a Si substrate. Conversion to oxide was done by annealing at temperatures ranging from 400oC to 1000oC for 15 minutes in argon. The samples were quenched to room temperature. Chemical analysis via X-ray diffraction methods and Raman spectroscopy indicated that CeO2 formed on the substrate after annealing. Structure and phase composition of the films, after heat treatment, were strongly temperature dependent. Surface morphologies were characterized by field emission scanning electron microscope. The morphologies were strongly dependent on the initial cerium salts being used and temperature of annealing. Films fabricated via cerium(III) nitrate showed apparent cracking and peeling.